(untitled) (Research, Society and Development, 2022)
Land concentration, injustices in the countryside, and the struggle for the right to land have marked the lives of many rural families over the centuries. Thus, the existence of public policies that enable this population, "invisible" to the latifundium, to have access to land is essential as a means of reducing the social inequality and misery present in the countryside. The aim of the study was to get to know the socioeconomic conditions and quality of life of families settled by the National Land Credit Program (NLCP) in the Rancho Alegre settlement in Candeias do Jamari, Rondônia. The data survey was carried out through the application of a semi-structured socioeconomic questionnaire, applied to 30 families, in October 2021 and February 2022. Under the conditions observed, the Rancho Alegre settlement does not have a basic sanitation system. Most families pointed out as a major problem of the settlement the absence of a school unit, as well as health posts, hindering their well-being. Regarding the infrastructure of the lots, most of the houses are made of wood, covered with asbestos tiles and all have access to electricity. As for production, vegetables are the main products produced. All the plots received technical assistance in the first five years, provided by the NLCP.